2016
DOI: 10.1007/s00384-016-2639-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the microbiome in children’s appendicitis

Abstract: Background/aimThe role of the microbiome has been widely discussed in the etiology of appendicitis. The primary aim was to evaluate the microbiome in the normal appendix and in appendicitis specifically divided into the three clinically and histopathologically defined grades of inflammation. Secondary aims were to examine whether there were any microbiome differences between proximal and distal appendices, and relate the microbiome with histopathological findings.MethodsA prospective pilot study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 37 publications
5
51
0
8
Order By: Relevance
“…A number of prospective studies of children were conducted to find urinary biomarkers for AA, such as leucine-rich α-2-glycoprotein (LRG), not to be used alone but combined with PAS and routine blood tests. LRG in conjunction with PAS showed 95% sensitivity, 90% specificity, 91% positive predictive value, and 95% negative predictive value for AA in children [62].…”
Section: Q14: What Is the Role Of Serum Biomarkers In Evaluating Pementioning
confidence: 95%
“…A number of prospective studies of children were conducted to find urinary biomarkers for AA, such as leucine-rich α-2-glycoprotein (LRG), not to be used alone but combined with PAS and routine blood tests. LRG in conjunction with PAS showed 95% sensitivity, 90% specificity, 91% positive predictive value, and 95% negative predictive value for AA in children [62].…”
Section: Q14: What Is the Role Of Serum Biomarkers In Evaluating Pementioning
confidence: 95%
“…Martin Salö et al conducted a study of 3 control samples, 11 phlegmonous samples, 4 gangrenous samples and 4 perforated samples. They also utilized 16S rRNA gene sequencing but did not observe a signi cant difference among the different groups (8). Our results demonstrated that there was not signi cant difference in the microbiota between the non-perforated and perforated appendicitis groups, suggesting that antibiotic selection does not need to be altered based on bacterial culture results.…”
Section: Discussionmentioning
confidence: 63%
“…Alexander Swidsinski's group applied rRNA-based uorescence in situ hybridization to investigate sections of 70 appendixes, and their results supported the hypothesis that the local microbiota was responsible for the occurrence and development of appendicitis (7). However, some scholars believe that there is no correlation between local microbiota and the grade of in ammation (8). Moreover, it is di cult to explain why although the results of bacterial cultures were different, patients recovered similarly after treatment with appendectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion surrounding the removal of the appendix in cases of rotation anomalies of the intestine has proven to be controversial. On the basis of infectious-immunological reasons, we prefer not to remove the appendix, as it is a space for the normal intestinal flora to reside during enteritis [32] [33]. Nevertheless, parents and, depending on the case, an intelligent child should be made aware of the possibility of left-sided appendicitis [34].…”
Section: Malrotation Volvulusmentioning
confidence: 99%